The Problem of Musyrif in the Development of the Character of Mahasantri in Ma'had Al-Jami'ah - Siregar, Rahmadani (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2025)
This study aims to identify the problems faced by the musyrif in fostering the character of students at Ma'had Al-Jami'ah, Sheikh Ali Hasan Ahmad Addary State Islamic University of Padangsidimpuan, seen from the aspects of competence, workload, age, and communication skills. This research uses a qualitative method with an inductive approach. Data was obtained through observation, in-depth interviews, and document analysis. The results of the study show that: (1) from the competency aspect, some musyrif do not have sufficient experience and ability in character development; (2) from the aspect of workload, dense academic activities cause character development to not be carried out optimally; (3) from the aspect of age, the proximity of age between the musyrif and the student creates obstacles in the coaching process; and (4) from the aspect of communication, some musyrif still lack confidence in communicating in public. This research emphasizes the need to improve the competence and communication skills of the musyrif so that the development of the character of students can run more effectively.